Menerapkan Business Process Management untuk Meningkatkan Kolaborasi Tim dan Inovasi - Wulan Saraswati; Jeni Susyanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Business Process Management (BPM) has evolved from an efficiency improvement tool to an organizational strategy that supports digital transformation. As organizational needs for adaptability and creativity increase, the ability to collaborate across teams and innovate becomes a key success factor. This research aims to analyze the application of BPM as a means of improving team collaboration and innovation based on the latest trends (2024-2025). This study uses a qualitative approach through literature review and recent case studies in the technology and manufacturing sectors. The results show that BPM supported by digital technologies such as low-code platforms and AI can strengthen team synergy, accelerate decision-making, and produce competitive new products or processes.